BCCT: A GUI Toolkit for Brain Structural Covariance Connectivity Analysis on MATLAB - Xu, Qiang; Zhang, Qirui; Liu, Gaoping; Dai, Xi-jian; Xie, Xinyu; Hao, Jingru; Yu, Qianqian; Liu, Ruoting; Zhang, Zixuan; Ye, Yulu; Qi, Rongfeng; Zhang, Long Jiang; et al. (Frontiers in Human Neuroscience, 2021)
Brain structural covariance network (SCN) can delineate the brain synchronized alterations in a long-range time period. It has been used in the researches of cognition or neuropsychiatric disorders. Recently, Causal analysis of structural covariance network (CaSCN), Winner-Take-All & Cortex-Subcortex Covariance network (WTA-CSSCN), and Modulation analysis of structural covariance network (MOD-SCN), have expended the technology breadth of SCN. However, the lack of user-friendly software limited the further application of SCN for the researches. In this work, we developed the Graphical User Interface (GUI) toolkit of brain structural covariance connectivity based on MATLAB platform. The software contained the analysis of SCN, CaSCN, MOD-SCN and WTA-CSSCN. Also, the group comparison and result showing modules were included in the software. Furthermore, a simple showing of demo dataset was presented in the work. We hope the toolkit could help the researchers, especial the clinical researchers, to do the brain covariance connectivity analysis in the further work more easily.